Selective social learning in infancy: looking for mechanisms. Issue 3 (30th August 2017) - Crivello, Cristina; Phillips, Sara; Poulin‐Dubois, Diane
Abstract: Although there is mounting evidence that selective social learning begins in infancy, the psychological mechanisms underlying this ability are currently a controversial issue. The purpose of this study is to investigate whether theory of mind abilities and statistical learning skills are related to infants' selective social learning. Seventy‐seven 18‐month‐olds were first exposed to a reliable or an unreliable speaker and then completed a word learning task, two theory of mind tasks, and a statistical learning task. If domain‐general abilities are linked to selective social learning, then infants who demonstrate superior performance on the statistical learning task should perform better on the selective learning task, that is, should be less likely to learn words from an unreliable speaker. Alternatively, if domain‐specific abilities are involved, then superior performance on theory of mind tasks should be related to selective learning performance. Findings revealed that, as expected, infants were more likely to learn a novel word from a reliable speaker. Importantly, infants who passed a theory of mind task assessing knowledge attribution were significantly less likely to learn a novel word from an unreliable speaker compared to infants who failed this task. No such effect was observed for the other tasks. These results suggest that infants who possess superior social‐cognitive abilities are more apt to reject an unreliable speaker as informant. A video abstract of this article can be viewed at:https://youtu.be/zuuCniHYzqo Abstract : This study investigated whether theory of mind and statistical learning abilities are related to infants' selective social learning. Findings showed that infants who passed a theory of mind task assessing knowledge attribution were less likely to learn a new word from an unreliable speaker in comparison to infants who failed this task. No such effect was found with statistical learning skills.